2013
DOI: 10.1186/1423-0127-20-60
|View full text |Cite
|
Sign up to set email alerts
|

Substantial increase in the frequency of circulating CD4+NKG2D+ T cells in patients with cervical intraepithelial neoplasia grade 1

Abstract: BackgroundThe NKG2D receptor confers important activating signals to NK cells via ligands expressed during cellular stress and viral infection. This receptor has generated great interest because not only is it expressed on NK cells, but it is also seen in virtually all CD8+ cytotoxic T cells and is classically considered absent in CD4+ T cells. However, recent studies have identified a distinctive population of CD4+ T cells that do express NKG2D, which could represent a particular cytotoxic effector population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…We have previously reported an increase of CD4 + NKG2D + T cells in patients with low-grade cervical intraepithelial neoplasia, which might be the result of a chronic exposure to viral and/or pro-inflammatory factors [ 33 ]. In this context, different groups have addressed the effect of host pro-inflammatory responses in human papillomavirus (HPV)-related diseases [ 29 , 34 ], which might promote lesion progression to more advanced stages and affect tumor fate by diverse mechanisms including the direct participation of unusual immune cells, as would be the case of the CD4 + NKG2D + T cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported an increase of CD4 + NKG2D + T cells in patients with low-grade cervical intraepithelial neoplasia, which might be the result of a chronic exposure to viral and/or pro-inflammatory factors [ 33 ]. In this context, different groups have addressed the effect of host pro-inflammatory responses in human papillomavirus (HPV)-related diseases [ 29 , 34 ], which might promote lesion progression to more advanced stages and affect tumor fate by diverse mechanisms including the direct participation of unusual immune cells, as would be the case of the CD4 + NKG2D + T cells.…”
Section: Resultsmentioning
confidence: 99%
“…Compelling evidence by our group recently demonstrated an increase of CD4 + NKG2D + T cells in patients with low-grade cervical lesions, even when overall levels of CD4 + T cells did not increase. Also, in that study it was found that while TGF-β1 was significantly decreased in patients compared to healthy donors, both TNF-α and IL-15 showed a tendency to increase [ 33 ]. Thus, with these findings we believe that the expansion of CD4 + NKG2D + T cells in premalignant cervical lesions might be under the control of factors that are not well characterized at the moment, and that this population might be also expanded in established cancerous lesions of uterine cervix.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the existence of a large proportion of CD4+ NKG2D+ cells has been reported in neurological disorders associated with HTLV-1, as well as seropositive individuals human cytomegalovirus [18]. Study of Garcia-Chagollan et al (2013) [36] observed an increase in the population of CD4+ NKG2D+ in patients with cervical cancer. Groh et al (2003) [37] speculates that these CD4+ NKG2D+ T cells are apparently influenced by pro-inflammatory cytokines such as IL-15 or TNF-α, promoting a cytotoxic response against cells with aberrant expression of MIC molecules.…”
Section: Discussionmentioning
confidence: 98%
“…Importantly, studies have indicated a high prevalence of mortality, recurrence and metastasis of CRC to be associated with immunocompromised patients [3, 4]. One epidemiologic survey showed low activity of natural killer (NK) cells to be associated with an increased risk of cancer [5, 6], and that infiltration of CD8 + T cells and NK cells are closely related to the clinical outcome of CRC [7]. One study demonstrated that NK cells can kill human tumor cells isolated immediately from colon carcinomas [8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, NK cells can serve as effective immunotherapy for patients with metastatic CRC. For example, the adoptive transfer of NK cells to patients is an emerging method to treat the metastasis of CRC [6]. …”
Section: Introductionmentioning
confidence: 99%